Level of satisfaction of farmers and consumers towards supply chain management of horticultural products - C.PADMA VENI, M.BHAVYA MANJARI, M.SURYAMANI and (The Journal of Research, PJTSAU, 2017)
The horticulture scenario of the country is rapidly revolutionizing. India ranks first in the world in the combined production of fruits and vegetables. Supply Chain Management results in lower transaction costs and increased margins. Farmers are back bone for supply chain management to provide better produce to the consumer and also producer continues to be the dominant consumer. A scale was developed to measure the satisfaction level of farmers and consumers towards supply chain management of horticultural products based on Likert Method of Summated Ratings. Majority of the farmers had medium to high level of satisfaction towards Supply Chain Management of Horticultural Products. About 60 % of the consumers had high level satisfaction towards Supply Chain Management of horticultural products.